POTENTIAL IMPACT OF LETHAL AUTONOMOUS WEAPON SYSTEMS ON STRATEGIC STABILITY AND NUCLEAR DETERRENCE IN SOUTH ASIA - Maryyum Masood; Muhammad Ali Baig (Margalla Papers, 2023)
Several trends show that the efforts to alter South Asian strategic landscape have increased, which primarily includes unprecedented proliferation of technology to India. This has exacerbated Pakistan’s security dilemma and is a matter of significant concern for South Asian security environment. Militaries worldwide are preparing for a new warfare trend in emerging technologies that include artificial intelligence and machine learning-based autonomous weapon systems, robotics, hypersonic weapons, and quantum technologies. These technologies are expected to change the character of war besides affecting geopolitical competitions and rivalries. It is pertinent to analyse the impact of these new technologies on regional rivalries to identify and implement effective solutions, thus mitigating potential risks and preventing the occurrence of a catastrophe. As several states are developing AI-based Lethal Autonomous Weapon Systems, capable of targeting without human supervision, possible exploitation of these technologies by nuclear-armed states may increase the risk of war leading to more aggressive nuclear postures. Such a risk would be higher in South Asia as the ballistic missile flight time would be less than ten minutes, and conventional military interactions of rival states could occur near a long border. The integration of autonomy into conventional weapons and nuclear systems has the potential to undermine strategic stability and will be a quick recipe for accidents and miscalculations. This study explores the region’s threat perceptions and analyses the potential use of LAWS and how it can impact nuclear deterrence and strategic stability of South Asia. This study hypothesizes that LAWS will lower the nuclear threshold in the region and undermine deterrence stability.